Eng2bik an English to Bicol translation engine - Ong, Rebecca U. (2000)
"If as one people speaking the same language they have begun to do this, then nothing they plan to do will be impossible for them." -- Geneses 11:6 This is a quote from one of the most read books in the world signifying the importance of language. A tool that is powerful enough to build human's tower of Babel, bring peace and unite everyone. A tool that is used for communication. It is a way for people to react and counter-react to situations around him. Because of this, several people have developed new ways to improve current communication tools. Ways such as the Internet, telephone lines, satellites, fiber optics, televisions and radio, are innovated and improved. Although such ways have been discovered, it would be of no use if people using it cannot comprehend the things that it does. In addition, through this aspect, language comes in again. More often than not, conflicts and arguments occur because of the lack of knowledge regarding some particular language or misuse of it. Even if both sides have the best intentions, arguments may still arise. All because they failed to understand the situation. Thus, for progress to happen in this age of global ties and increasing foreign trade, we must learn to communicate effectively. But before we can communicate effectively outside the country, we as Filipinos must first understand one of the many spoken dialects within the country but also those people wanting to understand those complicated dialects. This tool is a machine translator that will translate English text to Bicol text. Although English is just a second language to most Filipinos, almost all of us can understand the said language. Our study is a machine translator that aims to implement the translation of English texts into Bicol. Using the grammatical and syntactical tools of both languages, the translator aims to restate an English sentence into its grammatically and syntactically correct Bicol equivalent. This is to be done by using various computational theories on linguistics. In our case, the source language of the machine translator is English and the target language is Bicol. This is not just a case of translating one English word to its direct Bicol equivalent, but a way of expressing many implicit and intuitive translation rules that cannot easily be explicitly explained and enumerated. There are rules, but there are also many exceptions to the rules. We are aiming to comprehend the workings of the mind of a true Bicolano speaker and incorporate it to a machine that lacks one important aspect of translation-- intuition. The presence of an English-to-Bicol translator would greatly benefit those who have difficulty in understanding the Bicol dialect.